EXPERT SYSTEM OF DENTAL AND DIAGNOSIS DISEASES USING FORWARD CHAINING METHOD BASED ANDROID - Djamaludin, Djamaludin; Haryanto, Haryanto; Hasim, Yulia Karlina (Universitas Muhammadiyah Semarang, 2018)
Computers are one of the most important parts in improving Information Technology. Lack ofknowledge about dental and oral diseases can be overcome by an expert with his knowledge andexperience. The purpose of making this expert system is to transfer knowledge possessed by an expertinto the computer so that users save more time and cost. This system uses forward chaining methodthat is inference method using reasoning starting from the facts first to test the truth of the hypothesis.The case study of this system is done at Permata Cipondoh Clinic with android based with expertmenu for knowledge management, The results show that the forward chaining method is appropriatefor the diagnosis of dental and oral diseases, because in fact, the reasoning of a dental and oral diseaseexpert leads to the symptoms experienced by dental and mouth disease and then obtained the type ofdental and oral diseases. Keywords: Artificial Intelligence, Expert System, Teeth and Mouth, Forward Chaining